PERAN CAMAT DALAM PEMBERDAYAAN MASYARAKAT DI KECAMATAN KUBU BABUSSALAM KABUPATEN ROKAN HILIR TAHUN 2021 - ,, Afrizal; Rafi, M. (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
Problems in community empowerment are evident in the low level of community participation in programs, limited budget availability, and suboptimal coordination between institutions, resulting in sub-optimal results. Based on these conditions, this study aims to analyze the role of the sub-district head in community empowerment in Kubu Babussalam District, Rokan Hilir Regency in 2021. According to Gani et al., the focus of the study includes the sub-district head's role as an innovator, motivator, and facilitator, as well as the factors influencing its implementation. This study uses a qualitative descriptive method with data collection techniques through interviews, observation, and documentation. Data analysis techniques include data reduction, data presentation, and conclusions. The research results show that the sub-district head's role as an innovator is beginning to be seen through the development of programs based on local potential. However, implementation is hampered by budget constraints, minimal technical training, and low community participation. In terms of motivation, efforts to encourage participation through deliberations and social activities are evident, although this has not been implemented evenly. Furthermore, in his role as a facilitator, the sub-district head has attempted to coordinate communication between the community and government agencies, ensuring a more targeted empowerment program. Factors that influence. Keywords: Community Empowerment, Role of Government